2021
DOI: 10.2147/jaa.s325499
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Eosinophilic Inflammation in Adult Asthmatics with High Serum and Urine Levels of Leukotriene E4

Abstract: Background: Cysteinyl leukotrienes (CysLTs) are key mediators for bronchoconstriction, eosinophil recruitment and mucus production in the airways of asthmatic patients. To better understand the role of CysLTs in different asthma phenotypes, we compared the levels of arachidonic acid metabolites in relation to asthma control status and phenotypes in adult asthmatics on regular anti-asthma medications. Methods: A total of 137 adult asthmatics (47 with aspirin-exacerbated respiratory disease [AERD] and 90 asthmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“… 27 , 28 Urinary LTE 4 has been extensively studied as a reproducible biomarker determining the phenotype of AERD and reported to be elevated in patients with uncontrolled AERD. 29 , 30 Elevated levels of PEC or FeNO are also known for poor asthma control and risk factor for AE. 1 , 11 , 31 The present study demonstrated that EDN levels (plasma, urine, and sputum) are the most important factor predicting UA in patients with AERD, but not in those with ATA.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 Urinary LTE 4 has been extensively studied as a reproducible biomarker determining the phenotype of AERD and reported to be elevated in patients with uncontrolled AERD. 29 , 30 Elevated levels of PEC or FeNO are also known for poor asthma control and risk factor for AE. 1 , 11 , 31 The present study demonstrated that EDN levels (plasma, urine, and sputum) are the most important factor predicting UA in patients with AERD, but not in those with ATA.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are comparable to those of our previous studies in patients with AERD, which are characterized by moderate-to-severe asthmatic symptoms and persistent type 2/eosinophilic inflammation in upper and lower airway mucosa. 28 29 30 The mechanism of how epithelial antigens induce autoantibody production needs to be further clarified. The present study did not confirm the presence of B-cell clusters as the source of autoantibody generation, although some studies have demonstrated this finding in chronic inflammatory diseases such as rheumatoid arthritis and allergic granulomatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Serum and urine levels of LTE4/PGF2α were significantly higher in NERD patients than in ATA patients and healthy controls in a recent study. 27 Moreover, the discriminative value of NERD from ATA was slightly better in urinary LTE4/PGF2α than in urinary LTE4. Thus, cysLT/PGF2α may be a new diagnostic biomarker for NERD.…”
Section: Biomarkers Related To Aa Metabolismmentioning
confidence: 92%
“…Serum and urinary levels of LTE4 and LTE4/PGF2α remained high in NERD patients treated with LTRA and were related to eosinophilic inflammation and disease severity. 27 An additional treatment is warranted for NERD patients with sustained high levels of cysLTs despite LTRA treatment.…”
Section: Management Of Nerd and Application Of Biomarkersmentioning
confidence: 99%